Pemanfaatan limbah bulu ayam dan kulit kacang tanah sebagai bahan pembuatan kertas seni dengan penambahan naoh dan pewarna alami - RIYANTI, LIA ASTRI ANGGA, Drs. Aminaah Asngad, M.Si (2014)
Quill and peanut leather are not optimal waste utilization. Quill has a high fiber content and peanut leather contain high cellulose can be used as a material made of paper art. Teak leaves containing anthocyanins and papaya leaves containing chlorophyll is a natural dye so well used as a dye art paper. This research aims to determine the tensile strength and tear paper art from quill and skin peanuts by the addition of NaOH and natural coloring and organoleptic test. This research used an experimental method with a completely randomized design (CRD). With 2 factors: factor 1. Composition (A1 = quill 50%: 50% peanut leather), (A2 = 40% quill : 60% peanut leather), (A3 = quill 30%: 70% peanut leather);factor 2.Dye (B1 = without dye), (B2 = dye teak leaf), (B3 = dye papaya leaves). The highest tensile strength A1B3 treatment with 3.5802 N value by staining papaya leaves. The highest tear strength A1B1 treatment with tear resistance value of 9.2773 N without substance research color. The highest organoleptic test for texture panelists prefer A3B1 (Coarse), the highest in the treatment A3B3 color (dark green), the appearance of the highest fiber on treatment A1B2 (looks), and A panelist A1B3 (visually). The conclusions of the research is the difference of tensile strength and tear strength of paper art and sensory test is influenced by the composition of the material.